PROSES PERENCANAAN PEMBANGUNAN DI KELURAHAN BANJAR XII KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR TAHUN 2021-2022 - Oktavianti, Kurnia; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The development planning process is carried out to facilitate development and attract community aspirations to participate in the development planning process, such as development planning meetings, in order to find out existing problems. Development planning deliberations in Banjar. The research method uses a qualitative approach, as a research process that produces descriptive data in the form of written or spoken words from people and observable behavior. The qualitative approach is an approach that focuses on in-depth observation. The results of this research are about the development planning process carried out to capture aspirations and formulate policy direction. Development planning deliberations in Banjar Communication in the implementation of development planning deliberations was carried out by informing that a musrenbang would be held, and then establishing coordination with the community, where this communication was not optimal because not many people were present at the musrenbang. Keywords : Preparation of plans, Preparation of program plans, Implementation of plans, Supervision, Evaluation.